Moral message of tolerance in Coki & Muslim's Youtube podcast on Being Human - Jevon Putri Ayunovem Samino; Mochammad Arkansyah (DIGICOM : Jurnal Komunikasi dan Media, 2023)
Moral messages are an important part so that we can add knowledge about the value of life. Moral messages can be conveyed through means of communication, one of which is through mass media that are comprehensive for the community. Submission of information via YouTube can be done quickly, one of which is through Podcasts. This study aims to determine the contents of the moral message contained in the podcast from the perspective of Coki & Muslims about tolerance for diversity and sensitive comedy on YouTube "Menjadi Manusia". The research method used is a qualitative descriptive method using John Fiske's theory where in conducting this research it describes the emergency of tolerance in Indonesia which has resulted in persecution of Tretan and Coki contained in the podcast content and what moral message is contained therein. By conducting this research, the researchers found results that there is a lack of tolerance in Indonesia and the treatment of organizations, especially the persecution of certain parties they perceive as threats. Therefore, the researcher concludes that the younger generation must do something about this problem of tolerance according to their respective capacities and not become a group that just stays silent and allows intolerance to occur.